2018
DOI: 10.1093/jas/sky122
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii and Neospora caninum infection in sheep, goats, and fallow deer farmed on the same area1

Abstract: Toxoplasma gondii and Neospora caninum are coccidian parasites with a global distribution that cause reproductive failure and production losses in livestock. The seroprevalence of both parasite species in ruminants and Cervidae has been investigated worldwide and found to vary greatly. Studies carried out on mixed flocks with 3 ruminant species (sheep, goats, and fallow deer) living under the same conditions are excellent models for identifying any differences in the rate of infection with the 2 parasites betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In contrast, seropositivity and infection levels higher than 30% have been reported in other European studies (reviewed by Olsen et al., 2019; Santoro et al., 2019; Witkowski et al., 2015). There are limited data of T. gondii seroprevalence from fallow deer in European countries (Almeria et al., 2018; Bartova et al., 2007; Gauss et al., 2006; Moskwa et al., 2018). Similar to the present study, two previous studies in Spain showed the highest T. gondii seroprevalences in fallow deer compared to other wild ruminants (Almeria et al., 2018; Gauss et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, seropositivity and infection levels higher than 30% have been reported in other European studies (reviewed by Olsen et al., 2019; Santoro et al., 2019; Witkowski et al., 2015). There are limited data of T. gondii seroprevalence from fallow deer in European countries (Almeria et al., 2018; Bartova et al., 2007; Gauss et al., 2006; Moskwa et al., 2018). Similar to the present study, two previous studies in Spain showed the highest T. gondii seroprevalences in fallow deer compared to other wild ruminants (Almeria et al., 2018; Gauss et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Domestic cats and wild felids serve as definitive hosts of T. gondii, while dogs and wild canines play the role of definitive hosts of N. caninum. Other warm-blooded vertebrate animals (including birds) have been reported as intermediated hosts for both T. gondii and N. caninum (12)(13)(14). Various avian species play an important role in the life cycle of these parasites by serving as intermediate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer data are available for cervids. Variable prevalence rates have been reported worldwide (6.6-53.5%) [88]. A recent systematic review and meta-analysis assessed the seroprevalence of T. gondii in roe deer and red deer in Europe [84].…”
Section: Red Deer and Roe Deermentioning
confidence: 99%